Red Photoactivatable Genetic Optical-Indicators - Hussein, Wessal; Berlin, Shai (Frontiers in Cellular Neuroscience, 2020)
Emerging Genetically-encoded Ca2+-indicators (GECIs) are intensiometric reporters that increase in fluorescence when bound to Ca2+; highly suited for studying calcium-signaling in many cell types, notably neurons. Today, major efforts are devoted towards optimizing red-emitting (red fluorescent protein; RFP-based) GECIs (R-GECI), as these provide several advantages over GFP-based reporters, for instance increased imaging depth, reduced photodamage by longer imaging wavelengths and, in principle, are better suited for use with prevalent blue-absorbing Optogenetic tools (e.g., Channelrhodopsin). However, excessive fluorescence from intersecting neighboring cells in very dense tissues, notably the brain, hinder the ability to collect signals from single cells and their processes. This challenge can be addressed by photoactivatable (PA) fluorescent proteins that can be rendered fluorescent on demand by user-defined targeted light. This allows activation and, thereby, collection of fluorescent signals exclusively from desired cells and their processes, whilst leaving all neighboring cells in the dark (i.e., non-fluorescent). Nevertheless, there are no photoactivatable R-GECIs. Here, we sought to develop PA-R-GECIs. To do so, we initially explored a recently discovered phenomenon of Ca2+-independent increases in fluorescence (i.e., artefacts) in an emerging R-GECI, which has led us to rationally engineer several functional PA-R-GECIs. We also take advantage of our findings to quickly engineer a novel PA-RFP, namely PA-mRuby3.